El aprendizaje basado en juegos como revulsivo didáctico para mejorar la competencia comunicativa en el aula de lengua extranjera: una revisión de la literatura - Davide Capperucci; Juan Carlos Manzanares Triquet (Firenze University Press, 2022)
The search for the ideal teaching paradigm has, since ancient times, been one of the great challenges facing didactics in any of its areas. However, game-based learning has not enjoyed the necessary focus considering its enormous potential. This article offers a review of the literature on this technique with the aim of addressing, from a global perspective, both, its dimension and its pedagogical scope. In it, we will analyze its nature, its elements and we will detail the time needed for its correct application. Likewise, we will summarize the guidelines to optimize its use, providing, in addition, different tools for developing teaching resources that can be used in the foreign language classroom.